Membrane-based technologies for biohydrogen production: A review. (15th August 2022) - El-Qelish, Mohamed; Hassan, Gamal K.; Leaper, Sebastian; Dessì, Paolo; Abdel-Karim, Ahmed
Abstract: Overcoming the existing environmental issues and the gradual depletion of energy sources is a priority at global level, biohydrogen can provide a sustainable and reliable energy reserve. However, the process instability and low biohydrogen yields are still hindering the adoption of biohydrogen production plants at industrial scale. In this context, membrane-based biohydrogen production technologies, and in particular fermentative membrane bioreactors (MBRs) and microbial electrolysis cells (MECs), as well as downstream membrane-based technologies such as electrodialysis (ED), are suitable options to achieve high-rate biohydrogen production. We have shed the light on the research efforts towards the development of membrane-based technologies for biohydrogen production from organic waste, with special emphasis to the reactor design and materials. Besides, techno-economic analyses have been traced to ensure the suitability of such technologies in bio-H2 production. Operation parameters such as pH, temperature and organic loading rate affect the performance of MBRs. MEC and ED technologies also are highly affected by the chemistry of the membrane used and anode material as well as the operation parameters. The limitations and future directions for application of membrane-based biohydrogen production technologies have been individuated. At the end, this review helps in the critical understanding of deploying membrane-based technologies for biohydrogen production, thereby encouraging future outcomes for a sustainable biohydrogen economy. Highlights: Significance and impacts of deploying bio-hydrogen. Different membrane-based technologies for bio-hydrogen production have been discussed in detail. Membrane fouling is the main hurdle for membrane-based technologies. Techno-economic analyses give a propensity for further development in bio-hydrogen production.